2012
DOI: 10.1063/1.3677311
|View full text |Cite
|
Sign up to set email alerts
|

Spin-transfer-torque switching in spin valve structures with perpendicular, canted, and in-plane magnetic anisotropies

Abstract: We exploit canted anisotropies as possible means to enhance spin-transfer-torque (STT) and reduce switching currents. The STTs in spin-valve structures with perpendicular, canted, and, as a reference, in-plane magnetic anisotropies were studied. For perpendicular magnetic anisotropy and canted spin valves the thicknesses and number of Co and Pt layers were varied to obtain different angles of the magnetic anisotropy with respect to the sample plane. Point contact measurements were used to measure the change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Such materials allow for additional control of the magnetization dynamics in magnetic nanostructures [17,[21][22][23], and hint at yet improved STT-MRAM switching behavior and thermal stability [24][25][26][27][28][29]. For STOs, tilted materials offer a route to improve their microwave generation properties, both in terms of higher output power and low-to zero-field operation [17,[21][22][23]28,[30][31][32].Recently, tilted materials have also been shown to have potential for current-driven domain wall motion [33].…”
mentioning
confidence: 99%
“…Such materials allow for additional control of the magnetization dynamics in magnetic nanostructures [17,[21][22][23], and hint at yet improved STT-MRAM switching behavior and thermal stability [24][25][26][27][28][29]. For STOs, tilted materials offer a route to improve their microwave generation properties, both in terms of higher output power and low-to zero-field operation [17,[21][22][23]28,[30][31][32].Recently, tilted materials have also been shown to have potential for current-driven domain wall motion [33].…”
mentioning
confidence: 99%
“…Such multilayered cylindrical systems are applied in magnetic random access memories (MRAM) 1 and generally in spin valves. 2,3 The wire-based approach, however, being inspired by textile magnetic materials 4 or low-dimensional magnetocrystalline symmetries observed in epitaxial layers, 5 can offer novel magnetic shape anisotropies at micro-scale and also many scenarios for magnetization dynamics. Thus, this topic requires systematic research to warrant a deep understanding of the appearing phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent literature, there are some interesting reports of exotic magnetic states in wire-arrays and single objects. For example, stable onion states were examined in permalloy (Py) rectangular rings of size 1.5 lm  1 lm, with a rectangular cross-section of 250  250 nm 2 , by Subrami et al 6 Wang et al tested rectangular arrays of 1.15 lm  0.7 lm rings with a closely (100 nm) and a widely (500 nm) spaced option for packing, 7 and concluded that closer spacing influences transitions from vortex states into onion states and vice versa, due to more collective behavior of rings. Interesting systems of closely spaced squared Py dipole lattices of four-fold symmetry and iron (Fe) Kagome lattices (a special composition of interlaced triangles) of six-fold symmetry, interacting via dipolar fields, were studied by Remhof et al 8 and Westphalen et al 9 Importantly, they observed collective effects and interpreted occurrence of horseshoe and vortex states in terms of interactions between parallel and antiparallel magnetically ordered sublattices.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanoparticles are of technological interest, for example, for magnetic storage media, magnetic sensors, and MRAMs [1][2][3]. Since their overall anisotropy is governed by the shape anisotropy [4], tailoring a nanoparticle's form allows for adjusting its magnetic properties.…”
Section: Introductionmentioning
confidence: 99%